Generalized Anxiety Disorder in Younger and Older Children: Implications for Learning and School Functioning. - Jarrett, Matthew; Black, Anna; Rapport, Hannah; Grills-Taquechel, Amie; Ollendick, Thomas (Journal of Child & Family Studies, 2015)
Few studies have examined differences between younger and older children with generalized anxiety disorder (GAD). The current study examined differences between children with GAD who were younger than the typical age of onset (i.e., ages 7-9) and children with GAD who were within the age range for typical age of onset (i.e., ages 10-13). These groups, defined as 'younger' versus 'older,' did not differ on demographic variables, but the older group had lower intelligence quotients. At the same time, mean values for both groups fell within the average range. Older children with GAD generally reported similar levels of worry as younger children with the exception of greater school-related worry, trouble paying attention, and getting upset easily. Younger children reported greater harm avoidance than older children. Parent reports did not generally differ between groups with the exception of greater perfectionism in younger children and greater school competence issues for older children. Teachers reported greater learning problems and less happiness in older children. Overall, limited differences were found on GAD severity and impairment, but some differences were found on cognitive and school functioning variables (e.g., intelligence, school-related worry, learning problems, school competence) and parent-child agreement on worry. Further, such differences did not appear to be accounted for by comorbid disorders or other variables. Overall, these findings suggest that GAD may be associated with different characteristics in younger and older children. Future studies, particularly prospective studies, are needed to understand the development of GAD and associated impairments such as academic functioning.